Additives and Endocrine Disruptors in Cosmetic Products for Use by Children Under 2 Years Old: A Danger Not Mentioned in Advertisements - Evodie, Tshibola Ntumba; Eric, Kasamba Ilunga (European Journal of Applied Sciences, 2024)
Endocrine disruptors are exogenous substances that alter the functions of the endocrine system and therefore induce harmful effects on the health of an intact organism, its descendants, or populations. They are at the heart of current health concerns, associated with other additives such as dyes and perfumes that constitute a source of allergy in predisposed individuals. The objective of this study is to identify and give the danger of endocrine disruptors, allergens and dyes in common cosmetic products for infants. Our study is described as descriptive, cross-sectional with prospective collection, and included all childcare cosmetic products with a label providing information on the chemical composition and present on the Kolwezi market. In a total of 48 ranges of cosmetic products analyzed, we found 10 types of endocrine disruptors, 13 types of allergens and 6 classes of dyes. Parabens are the most present endocrine disruptors in baby cosmetic products, followed by fragrance; and powder, followed by soap, are the products that contain more endocrine disruptors. Limonene is the most present allergen followed by geraniol; And powder, soap followed by lotion are the products that contain the most. Tartrazine is the most present dye and especially in soaps and lotions. These exogenous substances cause harmful effects on human health, which are accentuated in the most fragile, such as infants.